2019
DOI: 10.1371/journal.pone.0200673
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of the role of the antibiotic biosynthesis regulator AbsA2 in Streptomyces coelicolor A3(2)

Abstract: The AbsA1-AbsA2 two component signalling system of Streptomyces coelicolor has long been known to exert a powerful negative influence on the production of the antibiotics actinorhodin, undecylprodiginine and the Calcium-Dependent Antibiotic (CDA). Here we report the analysis of a ΔabsA2 deletion strain, which exhibits the classic precocious antibiotic hyper-production phenotype, and its complementation by an N-terminal triple-FLAG-tagged version of AbsA2. The compl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
(65 reference statements)
0
9
0
Order By: Relevance
“…The regulator RedZ is at the top of the regulatory cascade governing expression of the genes involved in prodiginine biosynthesis. Multiple regulators are known to influence redZ expression, including DasR (59), ScbR2 (60), and GlnR (61), among others (62)(63)(64). These regulators sense N-acetylglucosamine, antibiotics (including prodiginines and actinorhodin), and cellular nitrogen levels, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The regulator RedZ is at the top of the regulatory cascade governing expression of the genes involved in prodiginine biosynthesis. Multiple regulators are known to influence redZ expression, including DasR (59), ScbR2 (60), and GlnR (61), among others (62)(63)(64). These regulators sense N-acetylglucosamine, antibiotics (including prodiginines and actinorhodin), and cellular nitrogen levels, respectively.…”
Section: Discussionmentioning
confidence: 99%
“… 2017 ) and antibiotic biosynthesis (Sheeler, MacMillan and Nodwell 2005 ; Lewis et al . 2019 ), such as mtrA / mtrB and absA1 / absA2 , respectively. In addition, the presence of nutrients such as N-acetylglucosamine derived from chitin prevents the activation of redZ through the action of DasR (Rigali et al .…”
Section: Discussionmentioning
confidence: 99%
“…This TCS was one of the first regulators of antibiotic production described in [ 51 ]. This system has been established as a negative regulator of the production of the antibiotics ACT, RED, and CDA [ 52 , 53 , 54 , 55 , 56 ], through the direct regulation of the specific regulators of the synthesis pathways actII-ORF4 , redZ, and cdaR [ 55 , 57 ]. In the case of the regulation of CDA synthesis, it has been observed that AbsA2 is also able to directly regulate several genes of the cda cluster [ 55 ].…”
Section: Two-component Systems Of Streptomyces Coelicolormentioning
confidence: 99%